PERAN LEMBAGA ADAT DALAM PENYELESAIAN KONFLIK SOSIAL DAN DAMPAKNYA TERHADAP KESEJAHTERAAN MASYARAKAT NEGERI WAAI KABUPATEN MALUKU TENGAH - Bakarbessy, Derek (Fakultas Ilmu Sosial dan Ilmu Politik, 2025)
This research examines the role of traditional institutions in social conflict resolution and their impact on community welfare in Negeri WAAI, Central Maluku Regency. Using a qualitative approach with case study methods, this research involves in-depth interviews, participatory observation, and focus group discussions with various stakeholders. The results show that traditional institutions play a strategic role in conflict resolution through mechanisms based on the local wisdom of